Transparent wood with phase change heat storage as novel green energy storage composites for building energy conservation. (10th May 2021) - Xia, Rongqi; Zhang, Weiye; Yang, Yingni; Zhao, Junqi; Liu, Yi; Guo, Hongwu
Abstract: Transparent wood is a great potential biomass building material with good insulation and optical properties for the rapid growth building energy consumption and increasing environmental problems. Transparent wood enhanced with phase change heat storage function could effectively utilize sunlight and thermal energy to further improve energy efficiency. In this study, epoxy resin compound with phase change materials polyethylene glycol (PEG) were impregnated into the delignified wood to prepare novel transmittance energy storage wood (TESW). Fourier transform infrared spectroscopy and scanning electron microscope measurements proved that the TESW ternary interface performed favorable compatibility by cross-linking network structure and hydrogen bond combination, which improved the TESW anti-leakage stability and thermal energy storage efficiency. Differential scanning calorimetry experimental results combined with heat conduction mechanism showed that the energy storage performance of TESW improved with the increased PEG content. The TESW with 80 wt% PEG regulated economic optimality high latent heats of 134.1 and 122.9 J/g at 30.66 and 22.19 °C during the energy storage/release stage, respectively. Optical testing showed the TESW obtained high light transmittance up to 80.89%, this manifested that the addition of energy storage function has slight influence on the photopermeability. This research offered a novel way for green energy storage composites fabrication, and the obtained TESW exhibits advantages of energy storage capacity and optical properties are promising for building energy conservation and indoor thermal comfort improvement. Graphical abstract: Image 1 Highlights: Provide a novel strategy for transparent wood with heat storage properties. The TESW with 80 wt% PEG exhibits optimum heat storage capacity. The transmittance of TESW can be up to 80.89%. The TESW favorable interface compatibility improved energy storage efficiency.